Evaluation of Lead and Cadmium Heavy Metal Residues in Milk and Milk Products Sold in Ogbomoso, Southwestern Nigeria - Tona, G.O.; Adetunji, V.O.; Ameen, S.A.; Ibikunle, A.O. (Pakistan Journal of Nutrition, 2013)
The concentrations of lead (Pb) and cadmium (Cd) heavy metals in cow milk, goat milk butterfat, soft cheese and yoghurt samples were evaluated. Forty samples (eight of each sample) were analyzed using the atomic absorption spectrophotometer. There were detectable residual concentrations of Pb and Cd in all the 40 samples. The range of 0.0025 to 0.0061 ppm of Pb concentrations in the samples was within the Maximum Residue Limit (MRL) of 0.0125 to 0.0175 ppm of Pb in milk and dairy products. There was a significantly (P0.05) different from that of the goat milk samples. Residual concentrations of Cd were higher in soft cheese samples (0.0048±0.0007 ppm) and in goat milk samples (0.0045±0.0005 ppm Cd) and these two concentrations exceeded the MRL of 0.0035 ppm of Cd recommended by India regulations. The residual concentration of Cd in goat milk samples (0.0045±0.0005 ppm) was significantly (P